The Length of Days : An Urban Ballad - Rafeyenko, Volodymyr (Harvard library of Ukrainian literature, 2023)
In The Length of Days, featuring a wild cast of characters, Rafeyenko combines poetry and wicked humor with elements of magical realism. The novel is set in 2014, mostly in the composite Donbas city of Z--an uncanny foretelling of what this letter has come to symbolize since February 2022, when Russia launched a full-scale invasion of Ukraine.